2019
DOI: 10.33165/rmj.2019.42.3.162035
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Foot Care Behaviors Among Patients With Type 2 Diabetes Mellitus in Da Nang, Vietnam

Abstract: Background: Foot ulceration and amputation have alarmingly increased among patients with type 2 diabetes mellitus in Vietnam. Poor foot care behavior is one of the crucial reasons which leads to diabetes related foot problems. Exploration factors related to foot care behaviors among people with diabetes becomes a necessary issue to limit this complication. Objective: To determine factors related to foot care behaviors among patients with type 2 diabetes mellitus. Methods: The descriptive correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
3
6
0
Order By: Relevance
“…This result was consistent with studies conducted in North Iran, and Bangalore with majority of their subjects had a low level of foot care behavior (Pourkazemi et al, 2020, Manjunath & Nandini, 2020. Another study by Sen et al (2019) also showed half of the participants had low footcare behavior. In Malaysia, it was consistent with a study in Kuantan, Pahang by Azmi et al (2020), which showed that half of the study subjects had poor foot care practice and poor awareness of foot care practice.…”
Section: Discussionsupporting
confidence: 90%
“…This result was consistent with studies conducted in North Iran, and Bangalore with majority of their subjects had a low level of foot care behavior (Pourkazemi et al, 2020, Manjunath & Nandini, 2020. Another study by Sen et al (2019) also showed half of the participants had low footcare behavior. In Malaysia, it was consistent with a study in Kuantan, Pahang by Azmi et al (2020), which showed that half of the study subjects had poor foot care practice and poor awareness of foot care practice.…”
Section: Discussionsupporting
confidence: 90%
“…This result was consistent with studies conducted in North Iran, and Bangalore with majority of their subjects had a low level of foot care behaviour (Pourkazemi et al, 2020, Manjunath & Nandini, 2020. Another study by Sen et al (2019) also showed half of the participants had low footcare behaviour. In Malaysia, it was consistent with a study in Kuantan, Pahang by Azmi et al (2020), which showed that half of the study subjects had poor foot care practice and poor awareness of foot care practice.…”
Section: Discussionsupporting
confidence: 90%
“…This finding was similar to several studies by Al-Gaows & Al-Zahrani (2019). In comparison, there was no significant association between gender and level of foot care in Vietnam and India by Sen et al (2019) and Pitchai & Joshi (2015). There are different foot care habits between males and females, which women usually wear improper footwear (Barwick et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Diabetic patients who couldn’t read and write and completed primary education were nearly two and three times more likely to have poor foot self-care practice compared with those who completed college and above education respectively. Similar findings were reported by studies conducted in Bahir Dar, Ethiopia, Kenya, Egypt, India, Vietnam, Indonesia, Jinnah Hospital, Lahore, and Baquba city, Iraq [ 23 , 30 , 33 , 34 , 37 , 38 , 41 , 42 , 47 ]. This could be because as a diabetic patient’s educational status improves, so will his or her awareness of foot self-care principles, which is the fundamental preventive measure of diabetic foot ulceration, which will be practiced regularly.…”
Section: Discussionsupporting
confidence: 90%